Invincible. [1], Family matters - Kirkman, Robert (Image Comics, 2006)
Mark Grayson is a senior in high school when he finds out he has superpowers inherited from his father. Mark learns to hone his skills as a superhero while calling himself "Invincible." Soon Mark meets other teenage superheroes and together they fight crime.